Challenges of India's power transmission system. (December 2018) - Upreti, Naveen; Sunder, Raju Ganesh; Dalei, Narendra N.; Garg, Sandeep
Highlights: IPTS is dogged with several challenges that limit the efficient power evacuation. The growth of entire power sector depends upon a robust and non-collapsible transmission network. Absence of strategic planning by policy makers emerged as a primary causal factor. Skewed focus of regulators towards generation has resulted in relatively low transmission investments. Adequate investment is needed to execute re-planning of the entire Transmission sector.